Impact of extruded feed ingredient on meat quality of broiler chickens: A meta analysis - Risyahadi Sazli Tutur; Retnani Yuli; Sukria Heri Ahmad; Sumiati; Jayanegara Anuraga; Sukarman Sukarman (BIO Web of Conferences)
Extruded-fed broilers can improve their performance by improving their digestibility, although its effect on meat quality has not been clarified. This study aims to evaluate the effects of extruded feed on broiler meat quality using meta-analysis. Literature was searched and screened using the Preferred Reporting Items for Systematic Reviews and Meta- Analysis (PRISMA) protocol. Data from seven articles with publication time between 2013 and 2024 were calculated using OpenMEE software to determine the hedges-D of the meta-analysis and interpreted using forest plot images. The results showed that extruded feed did not negatively influence meat quality parameters, such as UFA, SFA, TBARS, Omega-3, pH, drip loss, freshness, and yellowness (P>0.05). It can also improve quality by decreasing WHC and reducing total lipids (P<0.05). These results indicate that extruded feed can improve meat quality.